Effect of Salt Stress on Medicinal Plants and its Amelioration by Plant Growth Promoting Microbes - Mondal, Hemanta Kumar; Kaur, Harshpreet (International Journal of Bio-resource and Stress Management, 2017)
Salt stress is widely recognized as one of the important abiotic stressors results the severe reduction of medicinal plants growth and its herb yield. It also critically reduces the production of medicinally important active chemical content in the plants. There are three main stages on the growth of medicinal plants where the high salinity stress severely affects the plant growth. Recent studies showed that there is reduction of herb yield around 60% and simultaneous active chemical content reduction of around 50% under the exposure of high salinity of 300 mM of NaCl concentration. There are many reasons behind the reduction of growth of medicinal plants due to salt stress. There are also morphological, physiological and biochemical changes observed on the medicinal plants but there is still mystery exists whether any ultra-structural changes occur on the medicinal plants for salinity stress. The strategies employed in recent years to reduce the effect of high salinity stress on medicinal plant production mainly focused on a selection of salinity tolerant host genotypes. However, such efforts need high cost and inputs, there is an immediate urgency to build simple, low cost, sustainable and short term methods for salinity stress management. Hence the use of plant growth promoting microbes inhabiting rhizosphere, phyllosphere or endosphere might play a significant role in this aspect, if we exploit them as a multi-trait PGPR like stress-tolerant, PGPR activities, manipulation of signalling between both partners as plant and microbes with specific compatible solutes.